ANALISIS PENERAPAN PSAK 34 DALAM PENGAKUAN PENDAPATAN PERUSAHAAN JASA KONTRUKSI PADA PT ARTERI CIPTA RENCANA - Pahlevi, Lola Venna; Sari, Ratna; Ahmad, Hamzah (Invoice : Jurnal Ilmu Akuntansi, 2021)
The aims of this research are to analyze the application of work contracts and the recognition of revenue for construstion service companies in accordance with PSAK 34 at PT Arteri Cipta Rencana. The data required in this study is secondary data, namely the financial statements of PT Arteri Cipta Rencana project for the period 2017-2019. Methods of data collection through interviews, observation and documentary. Data analysis techniques used by qualitative analysis.  This result of this research show that that the implementation of PSAK 34 at PT Arteri Cipta Rencana had executed project contracts sequentially in accordance with the prevailing tender regulations and realized the budget appropriately. The recognition of income and expenses carried out by PT Arteri Cipta Rencana is in accordance with PSAK 34 where revenue recognition for construction contracts is carried out using the completed contract method in the short-term period in the 2016-2018 financial statements. This is in accordance with PSAK 34 applicable in Indonesia. Short-term projects using the completed contract method minimize the risk of errors in estimating the specified value. The financial statements are considered to have met the criteria for the quality of financial reports well.Keyword: PSAK 34, Construction Company and Revenue Recognition